1986
DOI: 10.1159/000284452
|View full text |Cite
|
Sign up to set email alerts
|

Positive and Negative Symptoms in Schizophrenia: Attentional Performance Correlates

Abstract: Attentional impairment has been hypothesized to be associated with negative symptoms in schizophrenia. The present study examined the relation between attentional performance and positive and negative symptoms in both schizophrenic and manic patients. The results showed that deficits on the distraction conditions of a digit-span task were greatest in positive-symptom schizophrenics. Regression analyses revealed that only certain positive symptoms were related to digit-span scores; specifically, ratings of posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
22
0
1

Year Published

1989
1989
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(28 citation statements)
references
References 21 publications
5
22
0
1
Order By: Relevance
“…Several authors have reported that individuals with schizophrenia have reduced pupillary responses (Granholm et al, 2000(Granholm et al, , 1997Steinhauer and Hakerem, 1992;Steinhauer and Zubin, 1982). This finding is consistent with the 'resource limitations hypothesis', which suggests that schizophrenia patients have a general diminishment in their 'pool' of available attentional resources when processing higher cognitive-load tasks (Granholm et al, 1996a(Granholm et al, ,b, 1997Nuechterlein and Dawson, 1984;Nuechterlein et al, 1986;Walker and Harvey, 1986). Granholm and colleagues (2000) recorded pupillary responses during a task that required attention to a large array of information (high processing load) vs. a low processing load task.…”
Section: Introductionsupporting
confidence: 52%
“…Several authors have reported that individuals with schizophrenia have reduced pupillary responses (Granholm et al, 2000(Granholm et al, , 1997Steinhauer and Hakerem, 1992;Steinhauer and Zubin, 1982). This finding is consistent with the 'resource limitations hypothesis', which suggests that schizophrenia patients have a general diminishment in their 'pool' of available attentional resources when processing higher cognitive-load tasks (Granholm et al, 1996a(Granholm et al, ,b, 1997Nuechterlein and Dawson, 1984;Nuechterlein et al, 1986;Walker and Harvey, 1986). Granholm and colleagues (2000) recorded pupillary responses during a task that required attention to a large array of information (high processing load) vs. a low processing load task.…”
Section: Introductionsupporting
confidence: 52%
“…In contrast, negative symptoms were uniquely and inversely related to the ability to process information under conditions of information overload. Walker and Harvey reported similar results (14).…”
Section: Objective: Previous Studies Of Attention/information Processmentioning
confidence: 56%
“…This finding testifies to the need of CPT versions with a high momentary processing load [19] to circumvent a ceiling effect and achieve meaningful results. Fur thermore it fits into a theoretical framework which regards a limited attentional capacity as the underlying substrate of many cognitive impairments in schizophrenia [28].…”
Section: Discussionmentioning
confidence: 99%